Neonatal glycine encephalopathy diagnosed by genetic sequencing: a case report - Narendra, Chandan Kalapanahalli; Pallithanam, Jis Jolly; Sreekumar, Kavita; Joshi, Vaishali (International Journal of Contemporary Pediatrics, 2025)
Non-ketotic hyperglycinemia (NKH), also known as Glycine encephalopathy, is a rare inborn error of metabolism (IEM) inherited in an autosomal recessive manner. Homozygous or compound heterozygous mutations in GLDC gene, a component of the mitochondrial glycine cleavage system that encodes the P protein, cause Glycine encephalopathy 1(GCE1). Whereas, mutation in the AMT gene, which codes for the T protein of the mitochondrial glycine cleavage pathway, results in glycine encephalopathy 2 (GCE2). In severe cases, symptoms can include lethargy, poor feeding, seizures, breathing difficulties and death. We report the case of a term neonate who presented with lethargy, poor feeding, hypotonia and seizures. Newborn metabolic screening was negative. Whole Exome Sequencing (WES) was done, which identified, a homozygous 1 base pair deletion in exon 7 of the GLDC gene, which is classified as likely pathogenic, for glycine encephalopathy. Baby was treated with sodium benzoate, dextromethorphan and supportive measures. A normal TMS does not exclude the possibility of glycine encephalopathy. The above case highlights the importance of genetic tests like WES in the diagnostic evaluation of suspected metabolic disorders. Early diagnostic confirmation through genetic studies is necessary for timely and accurate management, prognostication as well as for genetic counseling.